Achievement Responsibility and Its Relation to Self-determination Motivation of Foundation Program Students - Najah S. Al-Syabi; Abulqawi S. Al-Zubaidi; Ibrahim Al-Harthy; Ali Mahdi Kazem (Sultan Qaboos University, 2016)
The current study investigated the relation between achievement responsibility and selfdetermination motivation among foundation program students. It also aimed at identifying the differences in achievement responsibility and the self-determination motivation according to gender and the foundation level. The data was collected from 432 students. The results of the study showed that the students attributed their achievement to internal and unstable factors. Secondly, the students showed a quiet high level of selfdetermination motivation. Thirdly, the results showed no differences due to gender in both achievement responsibility and self-determination motivation. In regards to achievement responsibility, there were statistically significant differences in external and unstable factors according to the level variable for the second and third level. Regarding self-determination motivation, the results revealed statistically significant differences in external regulation and a motivation according to the level in favor of level two and three. The findings also suggested that the external factors seem to be the better predictor factor of self-determination motivation followed by the stable and finally the internal factors.